Automation Frameworks and Best Practices for Cloud-Native Database Lifecycle Management (International Journal of Scientific Research in Science and Technology, 2024)
The migration to cloud-native frameworks makes it imperative to effectively manage database lifecycle across organizations. Also, well developed and automated applications and web systems are needed for effectiveness and scalability of database that meets global standard. This study attempts a comprehensive review of best practices and automation frameworks for effective management of cloud-native database lifecycle. These include scaling, decommissioning, configuration, monitoring and provisioning. The study analyzes orchestration of container and the place of infrastructure as Code (IaC) in the automation of database operations in both public and private spheres of hybrid cloud-native environment. It also analyzes prominent managed services like Google Cloud SQL and Amazon RDS and tools like Kubernetes Operators and Terraform. In the course of the analysis, their strengths and weaknesses are highlighted. The article presents some practicable best practices capable of optimizing performance, ensuring regulatory compliance and safety, and minimizing operational bottlenecks. In all, the study has uniquely offered a realizable guidance to the concerned professionals on how to effectively streamline and manage database operations in changing cloud-native ecological spaces.